Offshore Technology Conference 1979
DOI: 10.4043/3434-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Yukon Delta: A Model for Deltaic Sedimentation in an Ice-Dominated Environment

Abstract: Field mapping in the Yukon delta region of western Alaska, combined with laboratory analysis of sediment and Landsat imagery, has provided insights into the role of climate and tectonics on delta ic processes on high-latitude continental sh~lves. The climatic and tectonic influences on sediment type, in combination with the role of river and sea ice in controlling patterns of sediment transport and deposition, suggest that the Yukon delta may provide a model for deltaic sedimentation in an ice-dcrninated envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…shows that wave and current energy is concentrated on the western margin of the delta which is exposed to the open Bering Sea and the full impact of southwesterly storm winds (Dupre and Thompson, 1979). 51 The results of our winter study strongly suggest that (1) tidal currents are the most important sediment transport agent during non-storm periods, in the summer as well as in the winter, and (2) a substantial amount of Yukon River sediment remains in the system at the close of the ice-free season.…”
Section: Discussionmentioning
confidence: 99%
“…shows that wave and current energy is concentrated on the western margin of the delta which is exposed to the open Bering Sea and the full impact of southwesterly storm winds (Dupre and Thompson, 1979). 51 The results of our winter study strongly suggest that (1) tidal currents are the most important sediment transport agent during non-storm periods, in the summer as well as in the winter, and (2) a substantial amount of Yukon River sediment remains in the system at the close of the ice-free season.…”
Section: Discussionmentioning
confidence: 99%
“…Jam formation may greatly constrict flow, causing it to discharge along an alternate, less-resistant course. Prowse (1998) and Dupre and Thompson (1979) suggested that ice-jam-induced avulsion plays a major role in shifting the distributary subchannels of river deltas.…”
Section: Channel Anabranching and Avulsionmentioning
confidence: 99%
“…3). As discussed by Dupre and Thompson (1979), clean sand on the Yukon Delta front is the result of wave reworking that removes the finer fraction.…”
Section: Texturementioning
confidence: 99%
“…Ice gouges, mixes, and deforms the substrate, and promotes current scour. Ice partially controls the geomorphology of the Yukon Delta (Dupr£ and Thompson, 1979). Sharpness of gouge morphology is highly dependent on the type of substrate being gouged.…”
Section: Age Of Ice Gougesmentioning
confidence: 99%
See 1 more Smart Citation